Pengaruh Budaya Kerja, Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Gaya Kepemimpinan Sebagai Variabel Moderasi Pada Dinas Sosial Kota Metro - Seftyan Dwi Putra; Yateno; Nina Lelawati (Jurnal Manajemen DIVERSIFIKASI, 2026)
This research aims to find out how work culture influences employee performance. To find out how work motivation influences employee performance. To find out how the work environment influences employee performance. To find out how the influence of work culture on employee performance is moderated by leadership style. To find out how the influence of work motivation on employee performance is moderated by leadership style. To find out how the work environment influences employee performance which is moderated by leadership style. The sample for this research was all employees at the Metro City Social Service, totaling 43 people. Data collection used questionnaires and literature studies, and data analysis used validity tests, reliability tests, normality tests, linearity tests, moderated regression analysis, T tests, and coefficient of determination (R2) tests using the program (SPSS). The results of the research show that there is a positive and significant influence on employee performance through work culture and work motivation, whereas in the work environment variable there is no positive and significant influence found and leadership style can moderate the influence of culture and work motivation on employee performance, but not the influence of the work environment on employee performance